Exploring EIL on Novice Teachers: The Inclusion of Local Culture-based Teaching Materials - Intan Pratidina Dewi; Dadang Sudana; Ahmad Bukhori Muslim (Journal of English Language Studies, 2022)
English as an International Language (EIL) paradigm has been discussed as the solution in decreasing the concern towards English native-speakerism in the EFL teaching materials. The English as an International Language (EIL) paradigm includes the familiarization to the English varieties and local culture-based teaching to lessen English native-speakerism. The following study identify novice teachers’ inclusion of the local culture-based items in their teaching materials through the reflection on experience and the belief of novice teachers towards English varieties and local culture-based items in their teaching of historical recount text. The case study design was utilized in the research with the pre-interview, document analysis, and post-interview of three novice teachers. The findings showed that participants had included the local culture-based in their adapted teaching materials, and supported the utilization of local culture-based teaching materials for students’ engagement and a better understanding of learning goals. However, participants still experience difficulties in fostering the students’ engagement to the local culture-based items, deciding between local culture-based and international exposure in their teaching materials, and retrieving teaching materials with the rigorous local culture-based materials.